Smart vehicle data logger using global positioning system and global system for mobile communication - Wan Mohd Amir Haris, Wan Sallehuddin (2008)
Nowadays, there are lots of technologies growing in this world. Technologies such as Global Positioning System ( GPS ), Global System for Mobile communications (GSM) and Multimedia card ( MMC ) can make our lives more comfortable. The Smart Vehicle Data Logger can track speed and location of the vehicle travel using Global Positioning System (GPS) and store the information into Multimedia Card. User is allowed to trace the location of the vehicle by SMS the Data Logger. The system will send back the location of the vehicle through GSM module. The controller for this prototype design is microcontroller system using PIC 18F452 and programmed using PIC C Compiler ( C Programming ) software. So, with these technologies, we can create an excellent way for fleet owners and managers to monitor their cars, trucks, or vehicles efficiently.